2008
DOI: 10.1007/s00415-008-0847-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral involvement in axonal Charcot-Marie-Tooth neuropathy caused by mitofusin2 mutations

Abstract: ■ Abstract Mutations in the mitofusin 2 (MFN2) gene are a major cause of primary axonal CharcotMarie-Tooth (CMT) neuropathy. This study aims at further characterization of cerebral white matter alterations observed in patients with MFN2 mutations. Molecular genetic, magnetic resonance imaging (MRI), magnetic resonance spectroscopy (MRS), and diffusion tensor imaging (DTI) investigations were performed in four unrelated patients aged 7 to 38 years with early onset axonal CMT neuropathy. Three distinct and so fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 37 publications
2
39
1
Order By: Relevance
“…These dynamic processes are of particular importance in neuronal cells because of their post-mitotic state and long processes with higher energy requirements, and dis-regulation in both fission and fusion proteins have been associated with central nervous system diseases [41,42]. In vertebrates, high-molecular weight GTPases, such as Mfn-1, Opa-1, Drp-1 and Fis-1, are key components involved in regulating the mitochondrial morphologic dynamics, and these factors have been linked to the cellular death program of apoptosis through the caspase associated pathway [43].…”
Section: Discussionmentioning
confidence: 99%
“…These dynamic processes are of particular importance in neuronal cells because of their post-mitotic state and long processes with higher energy requirements, and dis-regulation in both fission and fusion proteins have been associated with central nervous system diseases [41,42]. In vertebrates, high-molecular weight GTPases, such as Mfn-1, Opa-1, Drp-1 and Fis-1, are key components involved in regulating the mitochondrial morphologic dynamics, and these factors have been linked to the cellular death program of apoptosis through the caspase associated pathway [43].…”
Section: Discussionmentioning
confidence: 99%
“…[37][38] Predominantly periventricular white matter alterations at brain MRI have been described in MFN2-mutated patients. 10,39 While this study was under review, two independent patients with early onset CMT, also carrying a p.R104W Mfn2 amino acid change, were reported to present with optic atrophy, white matter MRI changes, and macrocephaly in one of them, although they did not show cognitive dysfunction at the ages of 16 and 7 years, respectively. 39 An impairment of brain mitochondrial function was suggested by the HEPs pattern at MRS in our patients.…”
Section: Molecular Genetic Analysismentioning
confidence: 99%
“…10,39 While this study was under review, two independent patients with early onset CMT, also carrying a p.R104W Mfn2 amino acid change, were reported to present with optic atrophy, white matter MRI changes, and macrocephaly in one of them, although they did not show cognitive dysfunction at the ages of 16 and 7 years, respectively. 39 An impairment of brain mitochondrial function was suggested by the HEPs pattern at MRS in our patients. This data are in keeping with the observation, made using CMT2A cell cultures, that although the mitochondrial network appeared morphologically unaltered, there was a significant defect of mitochondrial coupling, associated with a reduction of membrane potential.…”
Section: Molecular Genetic Analysismentioning
confidence: 99%
“…To date, four patients have been described. Züchner et al 5 found a patient with cerebellar peduncle involvement, Brockmann et al 7 described two patients with thalami and parieto-occipital lobe involvements and Chung et al 3 reported a patient with a frontal lobe lesion.…”
mentioning
confidence: 99%